An investigation of radiographers' and radiologists' perceptions and attitudes in Kuwait towards extending radiographers' role in mammography. Issue 2 (May 2022) - Muhanna, A.M.; Brown, P.N.; Pratt, S.
Abstract: Introduction: Kuwait has a shortage of radiologists, especially in mammography, resulting in increased workload and longer waiting times for women receiving imaging investigations. This study looked at how radiographers and radiologists perceived radiographers' role extension (RE) in mammography, and whether this could reduce radiologist workload, thereby improving patient service and waiting times. Methods: A single case study design with 10 radiographers (mammographers) and 10 radiologists was undertaken across multiple sites: hospitals, screening clinics and specialist centres in Kuwait. Data included individual semi-structured interviews, documentary analysis and field notes. Perceptions were examined under a theoretical framework, Abbotts' System of Professions. Results: Two main themes were identified, firstly in examining the current role of radiographers in mammography and areas of interest for extending role, this highlighted insufficient knowledge of the concept. The second focused on in-depth understanding of drivers and barriers to RE in mammography, both groups opposed radiographers performing extended tasks without radiologist supervision. Conclusion: Radiologists and radiographers' attitudes were influenced by concepts of professional identity and professional identity formation. Insufficient professional knowledge negatively affected the radiographers' readiness to undertake RE in mammography. Radiologists are reluctant to blur boundaries, enabling them to maintain and control jurisdiction of their own profession and that of radiographers, thereby, as discussed in Abbott's theory, limiting impact on workload or waiting times. Implications for practice: Whilst RE is limited, to improve workload and patient waiting times, setting up an educational programme for radiographers specialising in mammography would be an important step to extending the radiographers' role. The study highlighted a need to educate radiographers to undertake breast ultrasound and amend policy to introduce training programmes for radiographers. Radiographer rotation across the various radiographic modalities negatively affected radiographers' performance, placing well-trained radiographers permanently within the mammography department should improve experience and overall skills.